Use and correlates of VHA tobacco cessation counseling services by veterans with post-traumatic stress disorder. Issue 1 (20th March 2017) - Kelly, Megan; Wang, Shihwe; Rosenheck, Robert
Abstract : Purpose: Veterans with post-traumatic stress disorder (PTSD) have high lifetime rates of smoking and often have substantial difficulty quitting. However, relatively little research has focussed on the use of Veterans Health Administration (VHA) intensive tobacco cessation counseling services by veterans with PTSD and the characteristics of veterans with PTSD who do and do not use these services. The paper aims to discuss these issues. Design/methodology/approach: The present study is an analysis of national VHA administrative data fiscal year 2012 that identified utilization rates of VHA intensive tobacco cessation counseling among veterans with diagnoses of both PTSD and tobacco use disorder (TUD) ( N =144, 990) and the correlates of tobacco cessation counseling use. Findings: Altogether, 7, 921 veterans with PTSD diagnosed with TUD used VHA tobacco cessation services (5.5 percent). Veterans with PTSD who used tobacco cessation counseling services were more likely to have been homeless, to have a comorbid drug use disorder, and had used other VHA services more frequently than their counterparts who did not access tobacco cessation counseling. The use of outpatient mental health and substance use services was the strongest correlate of tobacco cessation counseling use by veterans in this sample. Notably, veterans with PTSD, TUD and HIV were more likely to engage in tobacco cessation services. Originality/value: This study demonstrates that future efforts should focus on increasing provider and veteran awareness of and accessibility to VHA intensive tobacco cessation counseling for veterans with PTSD.